The current state of the market of fitness services in the Republic of Kazakhstan and the city of Almaty (Journal of Economic Research & Business Administration, 2016)
The extensive growth in demand for fitness services in Kazakhstan, due to the promotion of healthy lifestyles, physical beauty, now an incentive to enhance the marketing activities of enterprises sports services. The study has the following objectives: to analyze the market of fitness services in the Republic of Kazakhstan and Almaty city; to study consumer preferences in the field of fitness services. The following methods were used for the task: collecting secondary data, SWOT-analysis. Also, the collection and processing of statistical data, publications, reports of foreign and domestic research and consulting companies, information-analytical portals. This paper presents an analysis of the main indicators of the Kazakhstan market of fitness services, namely supply and demand for fitness services (market size, growth rate, key players, market segmentation, etc.), as well as the current state of the market in the city of Almaty.
Keywords: fitness services; market analysis; segmentation.